Pengaruh Lingkungan Kerja, Keselamatan Dan Kesehatan Kerja, Serta Kompensasi Terhadap Komitmen Organisasi Karyawan Pada Bagian Produksi Di Pt. Sarihusada Generasi Mahardhika (SGM) Klaten - Rita Teguh Pupiati (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2020)
The purpose of this study is to describe 1) the effect of the work environment on employee organizational commitment, 2) The effect of occupational safety and health on employee organizational commitment, 3) Effect of compensation affects employee organizational commitment, 4) Effect of work environment, occupational safety and health, and compensation affects the organizational commitment of production department employees at PT. Sarihusada Generasi Mahardhika (SGM) Klaten. The study took samples from the company PT. Sarihusada Generasi Mahardhika (SGM) located in Klaten, Central Java. The sampling method is probability, and the sampling technique uses sampling quota. Data collection is done by distributing questionnaires to respondents. The number of questionnaires processed were 100 questionnaires. While the data analysis technique used is multiple linear regression analysis supported by F test, t test, R^2 test, and classical assumption test. The results of this study that with 0.05 significance showed a positive and significant influence between the work environments on organizational commitment. There is a positive and significant influence between occupational safety and health on organizational commitment. There is no positive and significant influence between compensation for organizational commitment. And the work environment, occupational safety and health, as well as compensation simultaneously have a positive and significant effect on the organizational commitment of production department employees at PT. Sarihusada Generasi Mahardhika (SGM) Klaten.